Skills and Human Resources Development in Improving Employee Performance - Nurhaeda Zaeni; Shandra Bahasoan; Haeranah Haeranah (Jurnal Manajemen Bisnis, 2021)
This study aims to test the influence of Skill and human resource development on the performance of Civil Servants at the Cultural Heritage Preservation Center of South Sulawesi. The data used questionnaires that were distributed to respondents. The data collectedusing the list of questions (indicators) submitted as a measuring instrument using modification of the likert scale. The sample of this study was a group of employees at the South Sulawesi Cultural Heritage Preservation Center of 100 respondents. Where all employees have different charateristics from high school education level to magister (S2) and based on work experience. Data analysis was conducted qualitatively and quantitatively using multiple linear regression methods. This method is used when conducting analysis on the influence of Skill and Human Resource Development on the Performance of Civil Servants at the Cultural Heritage Preservation Center of South Sulawesi. The result show that skill and development of human resources have a positive and significant effect on employee performance and, should routinely provide that Skill to its employees and has more attention to the performance of its employees. Employees who are considered to be underperforming, it is best to develop the employee.